Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai di RSUD Lakipadada Kabupaten Tana Toraja - Satrianto Sanggalangi; Dina Ramba’; Astriwati Biringkanae (CV. Ulil Albab Corp, 2024)
The aim of the research is to determine the influence of leadership style on employee performance at Lakipadada Hospital, Tana Toraja Regency. The type of research used in this research is quantitative research. The results of this research are that Leadership Style has a positive influence on Employee Performance at Lakipadada Hospital, Tana Toraja Regency with a calculated T value of 4.243> T table 1.663 with a significant value of 0.000 < 0.05, so H1 is accepted. The correlation coefficient value R is 0.170, which means that the relationship between leadership style has a very low relationship of 17.0% with employee performance. Meanwhile, the R2 value = 0.180, which means that the participative leadership style variable allocates contributions to employee performance variables with a value of 18.0%, the remaining 82% is influenced by other factors.